223k views
2 votes
If fg + 2f - g = 2 - (f + g), what is the value of g in terms of f?
Plz explain

User Redzo
by
5.4k points

1 Answer

0 votes

Answer:


$g=(2 -3f)/(f), f\\eq 0$

Explanation:


fg + 2f - g = 2 - (f + g)


fg + 2f - g = 2 - f - g

Add
g to both sides


fg + 2f = 2 - f

Add
-2f both sides


fg + 2f-2f = 2 - f -2f


fg = 2 -3f

Divide both sides by
f


$(fg)/(f) = (2 -3f)/(f) $


$g=(2 -3f)/(f)$

But
f can't be zero because it is undefined. So,


$g=(2 -3f)/(f), f\\eq 0$

User Michael Zlatkovsky
by
6.1k points